SYSTEMATIC REVIEW: POTENSI ANTI-INFLAMASI PADA TANAMAN PETAI (Parkia speciosa) - Ati, Viva Ratih Bening; Zahra, Rafika; Pristika, Alya; Hevatio, Dufvan; Widodo, Azzahra Wuri; Kinanti, Luhung Sekar; Munawir, Azzah Azizah; Widyasari, Ailsya Inaayah Putri (Mandala Of Health, 2024)
Anti-inflammatory is defined as a compound or class of drugs that has the activity of suppressing or reducing the inflammatory response. Inflammation is a dynamic body defense mechanism and can be acute or chronic. There are still many Indonesian people who self-medicate (self-medication) using modern and herbal medicine. One of the native Indonesian plants used as a herbal medicinal plant is petai (Parkia speciosa). One of the known benefits of petai is as an anti-inflammatory because of the flavonoid content in it. The aim of this research is to examine the potential anti-inflammatory activity of the petai plant (Parkia speciosa). This research method was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The articles used in this research came from databases such as Google Scholar, Pubmed, Semantic Scholar, Researchgate, Ebsco with the keywords used namely (Parkia speciosa) AND (stink bean) AND (anti-inflammatory). There were 8 articles taken for review. The conclusion is that petai (Parkia speciosa) seed, skin and leaf extracts have anti-inflammatory potential based on in vitro and in vivo tests.